Realizing Teracomputing, Proceedings Of The Tenth Ecmwf Workshop On The Use Of High Performance Computers In Meteorology. - Zwieflhofer, Walter (World Scientific, 2003)
Geosciences and in particular numerical weather prediction are demanding the highest levels of available computer power. The European Centre for Medium-Range Weather Forecasts, with its experience in using supercomputers in this field, organizes every other year a workshop bringing together manufacturers, computer scientists, researchers and operational users to share their experiences and to learn about the latest developments. This book provides an excellent overview of the latest achievements in and plans for the use of new parallel techniques in meteorology, climatology and oceanography. T.